The blue planet seas of life - British Broadcasting Corporation; Discovery Channel (Burbank, CA: BBC Video, 2001)
An exploration of Earth's oceans, focusing on the open ocean and the ocean floor
vol.1. Ocean world/Alasfair Fothergill - Frozen seas.- vol.2. Open ocean / produced by Andy Byatt - The deep / produced by Alasdair Fothergill.- vol.3. Seasonal seas/ produced by Andy Byatt - Coral seas / produced by Martha Holmes - vol.4. Tidal seas /produced by Andy Byatt - Coast / Alastair fothergill
Camera, Rick Rosenthal ... [et al.]; editor, Tim Coope ; music, George Fenton
Narrator, David Attenborough
Keywords: Ocean; Ocean bottom; Marine biology